Haplotype analysis of the X chromosome in patients with Turner syndrome in order to verify the possible effect of imprinting on selected symptoms - Vrtel, Petr; Vrtel, Radek; Klaskova, Eva; Vrbicka, Dita; Adamova, Katerina; Pavlicek, Jan; Hana, Vaclav; Hana, Vaclav; Soucek, Ondrej; Stara, Veronika; Lebl, Jan; Snajdrova, Marta; et al. (Biomedical papers, 2022)
Aims. Turner syndrome is the only chromosome monosomy that is postnatally compatible with life. The reported incidence of TS is 1 in 2500 liveborn girls. The phenotype of these girls is highly variable, with cardiac abnormalities being life-threatening defects. The aim of the study was to reveal the possible influence of the parental origin of the X chromosome in these patients on a selected phenotype that is associated with Turner syndrome. Selected symptoms and parameters were: a bicuspid aortic valve, aortic coarctation, lymphoedema, pterygium colli, coeliac disease, thyroiditis, otitis media, diabetes mellitus 2, renal abnormalities, spontaneous puberty, and IVF. Methods. The X chromosome haplotype was determined for a group of 45,X patients verified by native FISH. A molecular diagnostic method based on the detection of different lengths of X chromosome-linked STR markers using the Argus X-12 QS kit was used to determine the X haplotype. Results. Our results, analysed by Fisher's exact (factorial) test, suggest independence between the maternal/paternal origin of the inherited X chromosome and the presence of the anomalies that were studied (P=1 to P=0.34). Conclusion. In the group of 45,X patients, who were precisely selected by means of the native FISH method, no correlation was demonstrated with the parental origin of the X chromosome and the observed symptom.
Keywords: Turner syndrome; karyotype; phenotype; haplotype; chromosome X origin; imprinting